2013
DOI: 10.1063/1.4813913
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomorphic GeSn/Ge(001) quantum wells: Examining indirect band gap bowing

Abstract: A study of the bandgap character of compressively strained GeSn0.060-0.091/Ge(001) quantum wells grown by molecular beam epitaxy is reported. The built-in strain in GeSn wells leads to an increased separation between L and Γ conduction band minima. The prevalent indirect interband transitions in GeSn were probed by photoluminescence spectroscopy. As a result we could simulate the L-valley bowing parameter in GeSn alloys, bL = 0.80 ± 0.06 eV at 10 K. From this we conclude that even compressively strained GeSn/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 21 publications
6
63
0
Order By: Relevance
“…Further, it is expected that defectfree GeSn could be grown pseudomorphic (fully strained) onto relaxed Ge buffer layer or substrate with thickness below the critical thickness [15,16]. Recently, Alexander et al [17] studied the band gap character of compressively strained GeSn/Ge(001) quantum wells (QWs) grown by MBE and they demonstrated that these pseudomorphic layers could serve as active regions in light emitting devices in Ge-photonic circuits based on germanium-oninsulator substrates. GeSn p-i-n photodetectors with Sn contents up to 3.6% in active layer have been recently fabricated on Ge substrate with a cut-off detection wavelength reaching 1.95 µm [18].…”
Section: Introductionmentioning
confidence: 98%
“…Further, it is expected that defectfree GeSn could be grown pseudomorphic (fully strained) onto relaxed Ge buffer layer or substrate with thickness below the critical thickness [15,16]. Recently, Alexander et al [17] studied the band gap character of compressively strained GeSn/Ge(001) quantum wells (QWs) grown by MBE and they demonstrated that these pseudomorphic layers could serve as active regions in light emitting devices in Ge-photonic circuits based on germanium-oninsulator substrates. GeSn p-i-n photodetectors with Sn contents up to 3.6% in active layer have been recently fabricated on Ge substrate with a cut-off detection wavelength reaching 1.95 µm [18].…”
Section: Introductionmentioning
confidence: 98%
“…That peak may be related to a defect, such as dislocation in the Ge buffer layer. 37,38 Further investigation is needed to understand the type of the defect and the source of the emission. In Fig.…”
Section: Photoluminescencementioning
confidence: 99%
“…In fact, fully pseudomorphic Ge/Ge 1Ày Sn y interfaces have been demonstrated by several groups. [20][21][22][23][24][25] While these interfaces are defect-free, compressive strain is undesirable because it increases the direct gap energy and the direct-indirect separation, suppressing the two key benefits of Sn alloying. Moreover, Ge 1Ày Sn y films partially compressed or fully strained to Ge-buffer layers are of limited or no value as Ge stressors.…”
Section: Introductionmentioning
confidence: 99%